1995
DOI: 10.1111/j.1600-0447.1995.tb09785.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid levels of phenylacetic acid in mental illness: behavioral associations and response to neuroleptic treatment

Abstract: Cerebrospinal fluid levels of phenylacetic acid (CSF PAA) were obtained from normal controls and from drug-free psychiatric inpatients (schizophrenia, major depression, mania, and schizoaffective disorder). Post-treatment CSF PAA levels were obtained from 16 patients after 4 weeks of neuroleptic treatment. Phenylacetic acid levels were higher in women and were significantly correlated with age. There were no differences in CSF PAA levels between the various diagnostic groups and no difference between the paran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In that review, it was reported that CSF norepinephrine, prostaglandin E1, norepinephrine and PGE1 adenyl cyclase and platelet 5HT levels among persons with schizophrenia and schizoaffective disorder are similar, while platelet 5HT profiles are more alike among persons with bipolar disorder and schizoaffective disorder than those with schizophrenia. Subsequent studies of these sorts ( Table 5 ; Laruelle et al 1993 ; Sharma et al 1993 , 1994 , 1995 , 1997 , 1998 ; Faustman et al 1999 ) have generally observed no differences between persons with these conditions; instead, neurotransmitter abnormalities are more strongly associated with symptom severity (and particularly psychosis) as well as outcome measures (ie, length of hospitalization). Again, a dimensional approach to the study of these populations appears to inform more usefully on cerebral neurochemical abnormalities than categorical psychiatric diagnosis.…”
Section: Neurobiology Of Schizoaffective Disordermentioning
confidence: 99%
“…In that review, it was reported that CSF norepinephrine, prostaglandin E1, norepinephrine and PGE1 adenyl cyclase and platelet 5HT levels among persons with schizophrenia and schizoaffective disorder are similar, while platelet 5HT profiles are more alike among persons with bipolar disorder and schizoaffective disorder than those with schizophrenia. Subsequent studies of these sorts ( Table 5 ; Laruelle et al 1993 ; Sharma et al 1993 , 1994 , 1995 , 1997 , 1998 ; Faustman et al 1999 ) have generally observed no differences between persons with these conditions; instead, neurotransmitter abnormalities are more strongly associated with symptom severity (and particularly psychosis) as well as outcome measures (ie, length of hospitalization). Again, a dimensional approach to the study of these populations appears to inform more usefully on cerebral neurochemical abnormalities than categorical psychiatric diagnosis.…”
Section: Neurobiology Of Schizoaffective Disordermentioning
confidence: 99%
“…The study of PAA in psychiatric populations is motivated by the evidence that it is the main metabolite of 2-phenylethylamine (PEA), an endogenous biogenic tracer which has been found to be similar in structure and behavioral pharmacology to the psychostimulant amphetamine. PEA may therefore be implicated in the pathogenesis of schizophrenia and major depression …”
mentioning
confidence: 99%
“…PAA has been used to treat children with inborn errors of urea synthesis and also in patients with hyperammonemia [25, 26]. On the other hand, increased PAA levels have been associated with psychiatric illness [27]. Higher PAA levels induce cytostasis and modulate the synthesis and release of several growth factors including vascular endothelial growth factor [28,29,30].…”
Section: Discussionmentioning
confidence: 99%